New insights into synthesis of nanocrystalline hexagonal BN. Issue 12 (15th August 2020) - Matveev, A.T.; Permyakova, E.S.; Kovalskii, A.M.; Leibo, D.; Shchetinin, I.V.; Maslakov, K.I.; Golberg, D.V.; Shtansky, D.V.; Konopatsky, A.S.
Abstract: Uncovering the mechanism behind nanocrystalline hexagonal boron nitride ( h -BN) formation at relatively low temperatures is of great scientific and practical interest. Herein, the sequence of phase transformations occurring during the interaction of boric acid with ammonia in a temperature range of 25–1000 °C has been studied in detail by means of thermo-gravimetric analysis, X-ray diffraction, infrared spectroscopy, X-ray photoelectron spectroscopy, and high-resolution transmission electron microscopy. The results indicate that at room temperature boric acid reacts with ammonia to form an ammonium borate hydrate (NH4 )2 B4 O7 x4H2 O. Its interaction with ammonia upon further heating at 550 °C for 1 h leads to the formation of turbostratic BN. Nanocrystalline h -BN is obtained either during heating in ammonia at 550 °C for 24 h or at 1000 °C for 1 h. This result is important for the development of novel cost-effective and scalable syntheses of h -BN nanostructures, such as nanosheets, nanoparticles, nanofibers, and nanofilms, as well as for sintering h -BN ceramic materials. Graphical abstract: Image 1